SLAVERY, NEOLIBERALISM, NECROPOLITICS. THE SOLAR AND NOCTURNAL BODIES OF DEMOCRACY - Pietryka, Mateusz (Hybris, 2025)
The article explores the contemporary crisis of liberal democracy, framing it within the colonial heritage and ongoing economic dominance of Western countries. It traces the rise of the idea of human rights and free trade, linking it with the practices of slavery and exploitation of conquered territories. The author examines Enlightenment philosophers' views on slavery and colonialism and outlines the economic consequences of these historical phenomena to analyze how they contributed to the democratization and economic development of European countries. The text proceeds to examine current international economic relations to show how the imbalance of power between rich and developing countries leads to exploitation of the latter. The article argues that both colonial roots and contemporary unequal trade relations underpin the current rise of populism and xenophobia in Western countries faced. The main guiding theme of the work is Mbembe's proposed idea of the solar and nocturnal body of democracy: the constant intertwining of internal economic and cultural flourishing with the rise of inequality, populism and undemocratic practices.